Systems and Methods for Automated Treatment Recommendation Based on Pathophenotype Identification (2018)
A system and method are provided automated treatment recommendations based on pathophenotype identification. The computer system may receive variable values corresponding to a subject to which a clinical test has been applied and may normalize and vectorize these variables and may compare the resultant vector to centroids of predefined vector clusters. The computer system may assign the subject to a cohort corresponding to the vector cluster having a centroid with the shortest Euclidean distance to the vector. Based on this cohort, the computer system may generate and display prognostic information which may include any of: a recommended course of treatment, a pathophenotype corresponding to the cohort, risk of hospitalization of the subject, and an alert recommending hospitalization of the subject.